Desligamento humanizado: utopia ou realidade? - Lissot, Sandra Teresinha (Universidade do Vale do Rio dos Sinos, 2024)
The purpose of this study was to analyze how organizations can improve their dismissal processes to make them more humanized in the field of services. The study was carried out using a qualitative approach. The interviews were structured in two stages: the first stage identified the respondents' sociodemographic data, while the second utilized a semi-structured interview script to gain a clearer understanding of the specific objectives of this study. The sample consisted of HR managers, leaders, and workers in the same area, totaling 19 interviews. Among the main results, pertinent issues were identified, such as the role of culture expressed in strategic people management, which drives humanized management throughout the worker's journey in the organization until the moment when the link ends with the dismissal process. Leaders, who act as guardians of people management policies, play a crucial role in achieving a humanized dismissal. There is also a need to expand spaces for dialogue, both through the practice of feedback or other practices that stimulate dialogue, as well as collaborative practices that permit exchanges, clarity, and stimuli for self-reflection by all those involved. The contributions of this research also point to an understanding of the role of the people management area in organizations, considering the influence of its work in guiding and training leaders in the organization. This confirms the perception of the importance of the interactional dimension between leader and led during their journey in the organization, and recognizes that there are challenges that go beyond the organizational context, its purposes, and the involved stakeholders' expectations.
Keywords: Desligamento humanizado; Gestão de pessoas; Processo de desligamento; Processo de demissão; Humanized dismissal; People management; Termination process; Dismissal process; ACCNPQ::Ciências Sociais Aplicadas::Administração